Effects of pterostilbene on activities and protein expression of cytochrome P450 1A1 (CYP1A1) and glutathione s-transferase (GST) in benzo[a]pyrene-induced HT-29 colorectal cancer cell line - Ahmad Rohi Ghazali,; Lee, Wee Xian; Cheng, Xiang Yi; Asmariah Ahmad,; Tava Shelan Nagapan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Drug Metabolizing Enzyme (DME) has been a target of natural chemopreventive agents to inhibit, retard and reverse the process of carcinogenesis. Pterostilbene, an analog to resveratrol has been reported to possess various pharmacological benefits including chemoprevention. In our study, benzo[a]pyrene-induced HT-29 colorectal cell line was used as the DME model. The activity of phase I enzyme CYP1A as determined by the 7-ethoxyresorufin O-deethylation (EROD) assay was found to be inhibited significantly by pterostilbene at 50 μM, 75 μM and 100 μM (p ≤ 0.01, p ≤ 0.05, p ≤ 0.01 respectively) compared to the benzo[a]pyrene treated group. Meanwhile, pterostilbene induced glutathione-S-transferase (GST) activity significantly (p ≤ 0.01) at 50 μM as compared to the untreated. In addition, However, the protein expression of CYP1A1 and GST in pterostilbene treated group was not significantly affected compared to untreated. On the other hand, pterostilbene at 25 and 75 μM were able to increase the protein expression of transcription factor Nrf2 significantly (p ≤ 0.01). Results indicated that pterostilbene could reduce metabolic activation of procarcinogens and increase the detoxification process which can be potentially developed as chemopreventive agent.